GC-MS CHARACTERIZATION OF YEAST DEGRADED SOURSOP LEAF WAX ON ORGANIC SURFACE - YIRANKINYUKI, FAI F.; MAGAJI, BUHARI; ABDULLAHI, ABDULLAHI M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
The present investigation was carried out to characterize the compounds of yeast degraded soursop leaf wax on organic surface using Gas Chromatography-Mass Spectroscopy (GC-MS). The results of the GC-MS analysis provide different peaks revealing the presence of 28 phytochemical compounds with different therapeutic activities. All the new compounds formed from the yeast degraded soursop wax are useful compounds in pharmaceutical and chemical industries. Thus, Saccharomyces cerevisiae degradation of soursop wax has a good technoeconomic potential.